UMP Ink Seven MoU with strategic partner for the betterment of the community - Siti Sarah, Mohamad Rajimi (2017)
Collaboration between Universiti Malaysia Pahang and seven strategic partners empower all parties to strategically transforming the society through the commitment showed by governments, academicians, industries and communities in ensuring the success of communitising technology agenda which in line with the implementation of UMP Strategic Plan 2016-2020.